The Views of the Head of the Office of Religious Affairs (KUA) on the Lontong Kupang Isbat Nikah Program in Surabaya - Riany Ayuniemas Parisya Jenar; Mohammad Ikhwanuddin; Salman Alfarisi (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The Lontong Kupang Isbat Nikah program is a collaborative service between the Surabaya City Government, the Religious Court, and the Office of Religious Affairs (KUA) to assist couples who are married religiously but not yet legally registered. This study aims to explore the critical views of KUA heads in the five regions with the highest number of participants regarding the program's implementation. Using a qualitative approach, data were collected through in-depth interviews and observations. The results indicate that although the program provides a short-term administrative solution, most KUA heads are concerned about its long-term impact. They believe that the program's routine implementation could normalize the practice of unregistered marriages and undermine public awareness of the importance of officially registering marriages from the outset. Criticisms also focused on the weak verification system and the potential for procedural abuse. It was recommended that the program not be implemented annually, but rather only under certain circumstances with strict requirements. Several KUA heads even suggested a comprehensive reevaluation of the program, considering the possibility of its termination. In conclusion, despite its administrative benefits, the program needs to be reviewed to ensure it does not conflict with legal principles and the community's moral education.